CRYOCONSERVATION OF POTATO BREEDING CULTIVARS AT VIR - Y. V. Ukhatova; E. V. Oves; N. N. Volkova; T. A. Gavrilenko (Труды по прикладной ботанике, генетике и селекции)
Cryopreservation of 20 potato breading cultivars was carried out using an original modification of the DV-Biotech droplet vitrification method. The post-cryogenic regeneration frequency of the apical buds was significantly (p